Modulation of Gut Microbiota through Nutritional Interventions in Behçet’s Syndrome Patients: Preliminary Results from the MAMBA Study - Giuditta Pagliai; Silvia Turroni; Federica D’Amico; Irene Mattioli; Marta Tristan Asensi; Giacomo Emmi; Francesco Sofi (Proceedings)
Background. Recent evidence suggests that the gut microbiota (GM) in Behçet’s syndrome patients (BS) has low diversity and a peculiar layout. Diet is known to influence the GM, but to date no study has investigated its effect on these patients. Aim. To evaluate the effect of a lacto-ovo vegetarian diet (VD) and a Mediterranean diet supplemented with 2 g/die of oral butyrate (MD-Bt) in comparison with a Mediterranean diet (MD) on the GM in BS. Methods. Forty-four (27F; mean age: 46.9 ± 11.2 years) BS patients were randomly assigned to follow a VD, MD-Bt, or MD for 3 months each and then crossed over. Stool samples were collected from the participants at the beginning and at the end of each intervention phase. Samples were analyzed through 16S rRNA amplicon sequencing on an Illumina MiSeq platform. Results. Regarding alpha diversity, a decreasing trend after a VD (Shannon index: p = 0.069; observed species: p = 0.08) and an increasing trend after a MD (Shannon index: p = 0.084; observed species: p = 0.079) were observed. Regarding beta diversity, no significant separation was found between the sample groups either over time or between different interventions. Phylum-level taxonomic analysis showed a significant increase in Bacteroidetes (+2.6%; p = 0.049) following the MD and a significant reduction in Proteobacteria (−0.2%; p = 0.035) following the MD-Bt. At the family level, we observed a significant increase in Bacteroidaceae (+2%; p = 0.05) and Porphyromonadaceae (+0.3%; p = 0.004) after the MD, a significant reduction in Porphyromonadaceae (−0.4%; p = 0.05) and Rikenellaceae (−0.7%; p = 0.03) after the VD, and a significant reduction in Rikenellaceae (−0.2%; p = 0.008) and Turicibacteraceae (−0.02%; p = 0.04) after the MD-Bt. In addition, there was a significant increase in the genus Bacteroides (+2%; p = 0.05) and Parabacteroides (−0.2%; p = 0.004) after the MD. On the other hand, the MD-Bt, led to a significant increase in Clostridium (+1%; p = 0.05) and a significant reduction in Oscillospira (−0.6%; p = 0.011) and Turicibacter (−1.9%; p = 0.04). Conclusions. The MD appeared to have an overall better impact on the GM modulation of BS in terms of higher diversity and potentially beneficial compositional changes.